Watch your whiskers, stilton! / shipwreck on the pirates island eaudiobook - Stilton, Geronimo (Geronimo Stilton, 2017)
Two more exciting adventures from the internationally bestselling mouse who always gets the scoop—Geronimo Stilton!FORMAT: 2 CDs, UnabridgedNARRATOR: Bill Lobley The "famouse" reporter appears on a TV game show to save his newspaper and joins his sister on a haunted pirate treasure hunt in this pair of exciting adventures.